The comparison between foam rolling either combined with static or dynamic stretching on knee extensors’ function and structure - Kasahara, Kazuki; Konrad, Andreas; Yoshida, Riku; Murakami, Yuta; Sato, Shigeru; Koizumi, Ryoma; G Behm, David; Nakamura, Masatoshi (Biology of Sport, 2023)
Static stretching (SS) and dynamic stretching (DS) in combination with foam rolling (FR) have been attracting attention as warm-up routines in sports. However, the combined and intervention order effects of SS or DS and FR on flexibility, muscle strength, and jump performance are still unclear. Therefore, this study aimed to compare the combined effects of FR and SS or DS with the various intervention orders (i.e., SS + FR, DS + FR, FR + SS, DS + FR) on the function and properties of the knee extensors. Using a crossover, random allocation design, 17 male university students (21.0±1.1 y) performed four conditions combining FR and SS or DS. The measurement included knee flexion range of motion (ROM), pain pressure threshold (PPT), tissue hardness, maximum voluntary isometric contraction (MVC-ISO), maximum voluntary concentric contraction (MVC-CON) torque, and single-leg countermovement jump (CMJ) height of the knee extensors. All interventions significantly (p < 0.01) increased knee flexion ROM (SS + FR: d = 1.29, DS + FR: d = 0.45, FR + SS: d = 0.95, FR + DS: d = 0.49), and significantly (p < 0.01) decreased tissue hardness (SS + FR: d = -1.11, DS + FR: d = -0.86, FR + SS: d = -1.29, DS + FR: d = -0.65). There were no significant changes in MVC-ISO, MVC-CON, and CMJ height in all conditions, but a near significant, small magnitude (p = 0.056, d = -0.31) decrease of MVC-ISO was observed in the FR + SS condition. Our results showed that all the combinations of SS or DS and FR effectively decreased tissue hardness and increased ROM without decreasing muscle strength. Also, effect sizes indicated the largest increase in ROM and decrease in tissue stiffness after SS + FR without decreasing muscle strength and jump performance.